Produção de hidrocarbonetos através da síntese de Fischer-Tropsch utilizando catalisadores de Fe/K - Farias, Francisco Edson Mesquita (2007)
The Fischer-Tropsch synthesis has been focus of attention of the scientific and industrial community. This interest is related to the conversion of natural gas into high quality liquid products, such as gasoline and diesel, which have high commercial value. In this work the methodology applied to synthesize and characterize iron-based catalyst used in the Fischer-Tropsch synthesis was described. Emphasis was given to catalysts supported in silica and to industrial catalysts (used in the synthesis of ammonia) impregnated with potassium and copper. The catalysts were tested to identify more active and selective catalysts, changing the amount of structural promoter in order to optimize the product distribution of specific hydrocarbons (gasoline, diesel, wax). The reaction was carried out in a slurry phase reactor. The experiments followed a 22 factorial experimental planning with central point and the results were analyzed based on the surface response methodology. The effects of the operating conditions (temperature and pressure) and of the amount of potassium in the catalyst on the liquid product distribution were compared based on the chromatographs, number average number of carbons (Nn) and distribution dispersion. In all iron based catalyst used in the research, the number average number of carbons (Nn) increased with increasing amount of potassium in the catalyst formulation. This result indicates that the catalyst with 18 K supported in silica showed the highest degree of polymerization in comparison with all other catalysts produced in this research. The results showed that for the catalyst supported in silica high pressures (25 to 30 atm) favor the production of wax, while higher selectivity towards liquid fuels was favored by low pressure (20 atm) and low temperature (240ºC). For the industrial catalyst, an increase in the wax cat was observed at low temperatures (240-255ºC) and high pressures (30 atm). The experiments carried out with the both catalysts (silica-supported and alumina-supported) have presented significant amounts of n-paraffins with a maximum of 35 carbons and low dispersion of the product distribution which can be caused by space limitations within the catalyst pores.